2011
DOI: 10.1093/aobpla/plr007
|View full text |Cite
|
Sign up to set email alerts
|

Seed pre-treatment in rice reduces damage, enhances carbohydrate mobilization and improves emergence and seedling establishment under flooded conditions

Abstract: Priming rice seeds (soaking followed by drying) or soaking just before sowing improved emergence from flooded soil, reduced membrane damage from ROS and hastened carbohydrate mobilization. Most benefit was to lines with a superior ability to germinate in flooded soil even when untreated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
74
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(85 citation statements)
references
References 24 publications
6
74
0
5
Order By: Relevance
“…This emphasizes the importance of determining the right time of duration for priming depending on varieties if this technique was used to enhance the survival under submerged condition. However, Ella et al, (2011) have observed an enhancement of survival of AG-tolerant entries 'Kaiyan' and 'Khao Hlan On' under submerged condition when primed seeds were submerged for 24 hours. …”
Section: Experiments I: Seedling Survival Among Varieties When Normal mentioning
confidence: 94%
See 4 more Smart Citations
“…This emphasizes the importance of determining the right time of duration for priming depending on varieties if this technique was used to enhance the survival under submerged condition. However, Ella et al, (2011) have observed an enhancement of survival of AG-tolerant entries 'Kaiyan' and 'Khao Hlan On' under submerged condition when primed seeds were submerged for 24 hours. …”
Section: Experiments I: Seedling Survival Among Varieties When Normal mentioning
confidence: 94%
“…In contrast, hydro-priming decreased the survival of Mazhan Red compared to non-priming. According to Ella et al, (2011), priming is done to activate enzyme in germinating seeds before radical emergence. The poor survival rate of Mazhan Red may be due to early radical emergence during 24 hours of soaking and becoming dead during the drying process causing detrimental effect to the rate of survival under submergence.…”
Section: Experiments I: Seedling Survival Among Varieties When Normal mentioning
confidence: 99%
See 3 more Smart Citations